Faebound : a novel - El-Arifi, Saara (Del Rey, 2024)
"As a warrior in the elven army, Yeeran has known nothing but violence her whole life. Her sister, Lettle, is trying to make a living as a diviner, seeking prophecies of a better future. When a fatal mistake leads to Yeeran's exile from the Elven Lands, both sisters are forced into the terrifying wilderness beyond their borders. There they encounter the impossible: the fae court. The fae haven't been seen for a millennium. But now Yeeran and Lettle are thrust into their seductive world"--